A network analysis comparison of central determinants of body dissatisfaction among pregnant and non-pregnant women. (March 2020) - Fuller-Tyszkiewicz, Matthew; Broadbent, Jaclyn; Richardson, Ben; Watson, Brittany; Klas, Anna; Skouteris, Helen
Highlights: Overall body dissatisfaction was comparable for pregnant and non-pregnant women. However, pregnant women were more dissatisfied with some functional aspects of their body. Network analysis showed that areas of concern cluster together similarly across groups. Even so, several areas of concern were more or less influential for pregnant women. Abstract: The objective of the present study was to compare body dissatisfaction of pregnant ( n = 1245 overall; n = 320 trimester 1, n = 497 trimester 2, n = 428 trimester 3) and non-pregnant ( n = 547) women in terms of: (a) global dissatisfaction, (b) dissatisfaction with specific body parts/features, and (c) strength of inter-relation among these areas of dissatisfaction. While ANOVAs revealed small group differences in overall body dissatisfaction ratings for appearance and function, more sizable differences were observed at the item level. Network analysis showed that the dissatisfaction items clustered together in similar ways across groups, but that the relative importance of these items for the networks differed by group. In particular, dissatisfaction with chest was much less connected to other areas of dissatisfaction for pregnant women, whilst dissatisfaction with shape and/or weight were more strongly connected to other items for this group. Body function items were less important in the network for non-pregnant women. Findings support earlier qualitative findings suggesting that pregnant women are concerned with both appearance and functioning of their bodies. More broadly, information gleaned at the item level highlights the value in exploring areas of dissatisfaction that may increase understanding of global dissatisfaction ratings.